Testicular choriocarcinoma with cutaneous metastasis in a 19-year-old man - Toberer, Ferdinand; Enk, Alexander; Hartschuh, Wolfgang; Grüllich, Carsten (Journal of cutaneous pathology, 2018)
A 19-year-old man suffering from testicular choriocarcinoma presented to the dermatology department with a cutaneous metastasis on his head. This metastasis was the first sign of disease that led to medical consultation. Histopathology revealed cytotrophoblasts and syncytiotrophoblasts, the later expressing human chorionic gonadotropin antigen. Whole body computed tomography showed multiple metastases of the brain, lung, liver, bone, paraaortic lymph nodes and left uvea; the primary was found in the left testicle. Despite neurosurgical intervention and chemotherapy the patient died 9 days after the biopsy of the cutaneous metastasis. Cutaneous metastases of testicular choriocarcinoma are exceptionally rare, with fewer than a dozen cases reported in the English-language literature. The present case highlights that testicular choriocarcinoma metastatic to the skin should be included in the differential of cutaneous scalp tumors.